PET imaging of colony-stimulating factor 1 receptor: A head-to-head comparison of a novel radioligand, 11C-GW2580, and 11C-CPPC, in mouse models of acute and chronic neuroinflammation and a rhesus monkey - Zhou, Xiaoyun; Ji, Bin; Seki, Chie; Nagai, Yuji; Minamimoto, Takafumi; Fujinaga, Masayuki; Zhang, Ming-Rong; Saito, Takashi; Saido, Takaomi C; Suhara, Tetsuya; Kimura, Yasuyuki; Higuchi, Makoto (Journal of cerebral blood flow and metabolism, 2021)
Colony-stimulating factor 1 receptor (CSF1R) is a specific biomarker for microglia. In this study, we developed a novel PET radioligand for CSF1R, 11C-GW2580, and compared it to a reported CSF1R tracer, 11C-CPPC, in mouse models of acute and chronic neuroinflammation and a rhesus monkey. Dynamic 11C-GW2580- and 11C-CPPC-PET images were quantified by reference tissue-based models and standardized uptake value ratio. Both tracers exhibited increased uptake in the lesioned striata of lipopolysaccharide-injected mice and in the forebrains of AppNL-G-F/NL-G-F-knock-in mice, spatially in agreement with an increased 18-kDa translocator protein radioligand retention. Moreover, 11C-GW2580 captured changes in CSF1R availability more sensitively than 11C-CPPC, with a larger dynamic range and a smaller inter-individual variability, in these model animals. PET imaging of CSF1R in a rhesus monkey displayed moderate-to-high tracer retention in the brain at baseline. Homologous blocker (i. e. unlabeled tracer) treatment reduced the uptake of 11C-GW2580 by ∼30% in all examined brain regions except for centrum semi-ovale white matter, but did not affect the retention of 11C-CPPC. In summary, our results demonstrated that 11C-GW2580-PET captured inflammatory microgliosis in the mouse brain with higher sensitivity than a reported radioligand, and displayed saturable binding in the monkey brain, potentially providing an imaging-based quantitative biomarker for reactive microgliosis.Colony-stimulating factor 1 receptor (CSF1R) is a specific biomarker for microglia. In this study, we developed a novel PET radioligand for CSF1R, 11C-GW2580, and compared it to a reported CSF1R tracer, 11C-CPPC, in mouse models of acute and chronic neuroinflammation and a rhesus monkey. Dynamic 11C-GW2580- and 11C-CPPC-PET images were quantified by reference tissue-based models and standardized uptake value ratio. Both tracers exhibited increased uptake in the lesioned striata of lipopolysaccharide-injected mice and in the forebrains of AppNL-G-F/NL-G-F-knock-in mice, spatially in agreement with an increased 18-kDa translocator protein radioligand retention. Moreover, 11C-GW2580 captured changes in CSF1R availability more sensitively than 11C-CPPC, with a larger dynamic range and a smaller inter-individual variability, in these model animals. PET imaging of CSF1R in a rhesus monkey displayed moderate-to-high tracer retention in the brain at baseline. Homologous blocker (i. e. unlabeled tracer) treatment reduced the uptake of 11C-GW2580 by ∼30% in all examined brain regions except for centrum semi-ovale white matter, but did not affect the retention of 11C-CPPC. In summary, our results demonstrated that 11C-GW2580-PET captured inflammatory microgliosis in the mouse brain with higher sensitivity than a reported radioligand, and displayed saturable binding in the monkey brain, potentially providing an imaging-based quantitative biomarker for reactive microgliosis.